Ups and Downs of Trampoline Use by Children: Risks and Current Recommendations - Maria Luis Tomé; Inês Bileu Ventura; Maria Adriana Rangel (Publicaciones Permanyer, 2023)
The widespread increase in the recreational use of trampolines by children can be partially explained by the recent need to stay indoors during lockdowns due to the coronavirus disease 2019 pandemic. At the same time, there was a global increase in the number of pediatric accidents resulting from the domestic use of these devices. The resulting injuries may be severe, especially in younger age groups. Although the use of trampolines by children is discouraged in safety recommendations published by several scientific societies and some recent studies, there is still concern about the lack of knowledge about the risks of trampoline-related injuries. In this regard, this review article aimed to highlight the unique role of the pediatrician and / or family physician advising parents and caregivers as well as the general population to prevent trampoline-related accidents involving children.